Fungal Histidine Phosphotransferase Plays a Crucial Role in Photomorphogenesis and Pathogenesis in Magnaporthe oryzae - Mohanan, Varsha C.; Chandarana, Pinal M.; Chattoo, Bharat. B.; Patkar, Rajesh N.; Manjrekar, Johannes (Frontiers in Chemistry, 2017)
Two-component signal transduction (TCST) pathways play crucial roles in many cellular functions such as stress responses, biofilm formation, and sporulation. The histidine phosphotransferase (HPt), which is an intermediate phosphotransfer protein in a two-component system, transfers a phosphate group to a phosphorylatable aspartate residue in the target protein(s), and up-regulates stress-activated MAP kinase cascades. Most fungal genomes carry a single copy of the gene coding for HPt, which are potential antifungal targets. However, unlike the histidine kinases (HK) or the downstream response regulators (RR) in two-component system, the HPts have not been well-studied in phytopathogenic fungi. In this study, we investigated the role of HPt in the model rice-blast fungal pathogen Magnaporthe oryzae. We found that in M. oryzae an additional isoform of the HPT gene YPD1 was expressed specifically in response to light. Further, the expression of light-regulated genes such as those encoding envoy and blue-light-harvesting protein, and PAS domain containing HKs was significantly reduced upon down-regulation of YPD1 in M. oryzae. Importantly, down-regulation of YPD1 led to a significant decrease in the ability to penetrate the host cuticle and in light-dependent conidiation in M. oryzae. Thus, our results indicate that Ypd1 plays an important role in asexual development and host invasion, and suggest that YPD1 isoforms likely have distinct roles to play in the rice-blast pathogen M. oryzae.